A A Systematic Literature Review on the Implementation of Contextual Teaching and Learning at Various Levels of Education and Subjects in Indonesia (2022–2026) - Andi Kurnia Riski Sanneng; Rohati Rohati; Duano Sapta Nusantara (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aims to describe the progress, characteristics, and key findings regarding the implementation of the Contextual Teaching and Learning (CTL) approach in the 2022-2026 period through a Systematic Literature Review (SLR). Six articles that met the inclusion criteria were analyzed based on the year of publication, educational level, academic discipline, and research methodology used. The selection process was carried out through identification, screening, and inclusion steps according to SLR guidelines. The analysis findings indicate that CTL remains a relevant learning approach and has continued to be the subject of research over the past four years. The majority of studies focused on the junior high school level with Mathematics as the dominant subject, indicating that CTL is effective in helping students connect abstract concepts with real-world contexts. From a methodological perspective, CTL studies predominantly employed Research and Development (R&D) and quantitative approaches, followed by qualitative and mixed methods. Overall findings indicate that CTL has a positive impact on improving learning outcomes, conceptual understanding, and student engagement. Future research is recommended to expand the study to other levels and subjects to gain a more holistic view of CTL's effectiveness.